PENGARUH PENANGANAN KELUHAN TERHADAP LOYALITAS NASABAH PT. BANK MUAMALAT INDONESIA,TBK. DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL PERANTARA (STUDI PADA NASABAH BANK MUAMALAT CABANG SURABAYA) - Artanti, Yessy; Ningsih, Lestari (Benefit: Jurnal Manajemen dan Bisnis, 2010)
For many years Islamic banking industry has increased. One of player in Islamic banking competition is PT. MuamalatIndonesia. In service companies, the complaints are something that can not be avoided, in order to stay in competition, they must transform themselves continually to increasing handling of customer complaints as a determinant to create customer satisfaction. One of the advantages can be gained by the companies if the customers are satisfied, they will be a loyal customers. Measuring instruments used was a questionnaires, and datas are analyzed by Structural Equation Modeling. The results shows that handling of customer complaints toward customer satisfaction. While handling complaints do not directly affect customer loyalty.Â